2021
DOI: 10.1172/jci.insight.141323
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-receptor signaling regulates weight loss via central KLB receptor complexes

Abstract: Glucagon regulates glucose and lipid metabolism and promotes weight loss. Thus, therapeutics stimulating glucagon receptor (GCGR) signaling are promising for obesity treatment; however, the underlying mechanism(s) have yet to be fully elucidated. We previously identified that hepatic GCGR signaling increases circulating fibroblast growth factor 21 (FGF21), a potent regulator of energy balance. We reported that mice deficient for liver Fgf21 are partially resistant to GCGR-mediated weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 74 publications
(135 reference statements)
0
9
0
Order By: Relevance
“…Mice deficient for liver FGF21 are partially resistant to glucagon‐receptor‐mediated weight loss, indicating that FGF21 is a regulator of glucagon's weight‐loss effects. Mice deficient for neuronal βKlotho in the brain exhibit a partial reduction in body weight with chronic glucagon‐receptor‐agonism, indicating a role for central FGF21 signaling in glucagon‐receptor‐mediated weight loss (Nason et al, 2021).…”
Section: Fgf Signaling In the Brain And Sensory Organsmentioning
confidence: 99%
“…Mice deficient for liver FGF21 are partially resistant to glucagon‐receptor‐mediated weight loss, indicating that FGF21 is a regulator of glucagon's weight‐loss effects. Mice deficient for neuronal βKlotho in the brain exhibit a partial reduction in body weight with chronic glucagon‐receptor‐agonism, indicating a role for central FGF21 signaling in glucagon‐receptor‐mediated weight loss (Nason et al, 2021).…”
Section: Fgf Signaling In the Brain And Sensory Organsmentioning
confidence: 99%
“…We observed increased FGF21 levels in xGLP/GCG/gastrin (10 and 25 nmol·kg −1 ), xGLP/GCG‐15 and cotadutide treatment groups, but not in liraglutide and ZP3022 treatment groups (Figure S3A), compared with saline group, which is a selective action of the GCG component within the xGLP/GCG/gastrin, xGLP/GCG‐15 and cotadutide, as previous researchers have indicated in that both acute and chronic GCG receptor activation increase liver FGF21 expression and secretion (Habegger et al, 2013; Kim et al, 2018; Nason et al, 2021). The liver sections stained by H&E revealed that cotadutide, xGLP/GCG‐15 and xGLP/GCG/gastrin (10 and 25 nmol·kg −1 ) normalized hepatic lipid contents to a low level, whereas liraglutide and ZP3022 only decreased hepatic lipid contents to a medium level (Figure 6).…”
Section: Resultsmentioning
confidence: 54%
“…Means ± SD, n = 6. *P < 0.05 versus saline, a P < 0.05 versus liraglutide, cotadutide and ZP3022 expression and secretion(Habegger et al, 2013;Kim et al, 2018;Nason et al, 2021). The liver sections stained by H&E revealed that cotadutide, xGLP/GCG-15 and xGLP/GCG/gastrin (10 and 25 nmolÁkg À1 ) normalized hepatic lipid contents to a low level, whereas liraglutide and ZP3022 only decreased hepatic lipid contents to a medium level (Figure6).…”
mentioning
confidence: 91%
“…The GCGR is expressed by hepatocytes ( 5 ), where in addition to regulating hepatic glucose production, GCGR signaling reduces liver fat content by inducing lipid oxidation, augmenting metabolic enzyme activity, enhancing mitochondrial function, and increasing liver-specific metabolic rate ( 54 , 78 80 ). The importance of the liver in mediating the anti-obesity action of glucagon administration is exemplified by findings in liver-specific knockout models, where the absence of the GCGR ablates the ability of glucagon to induce weight loss ( 54 , 81 ). Together, these studies demonstrate that glucagon action augments energy expenditure and drives weight loss by GCGR activation in the liver; mechanistically, this is due to farnesoid X receptor (FXR)-mediated hepatic futile cycling (see Box 2 ), the secretion of the hepatokine fibroblast growth factor 21 (FGF21) and an induction of plasma levels of bile acid (BA) species known to impact energy homeostasis ( 54 , 63 ).…”
Section: Glucagon Targets the Liver To Increase Metabolic Ratementioning
confidence: 99%
“…In addition to its effect on BAs/FXR, glucagon rapidly and dose-dependently increases hepatic mRNA expression and circulating levels of the thermogenic hormone FGF21 in mice and adult humans ( 63 , 84 ). Notably, FGF21 and the FGF21 receptor complex (FGFR1c and KLB) knockout mouse models indicate that glucagon requires the FGF21 pathway to protect from obesity ( 54 , 63 , 81 ). Mechanistically, FGF21 acts via both central and peripheral mechanisms to leverage the energy-burning power of white and brown adipose tissue to augment metabolic rate in both a UCP1-dependent and -independent manner [see Box 2 ( 85 88 )].…”
Section: Glucagon Targets the Liver To Increase Metabolic Ratementioning
confidence: 99%